2006
DOI: 10.1007/s00213-005-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from continuous amphetamine administration abolishes latent inhibition but leaves prepulse inhibition intact

Abstract: These findings are similar to what was previously found with respect to an ESC AMPH regime. The only difference between the schedules was that the ESC AMPH schedule led to behavioural sensitization whereas the continuous AMPH did not. It is suggested that the expression of sensitization may not be a prerequisite for observed LI disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…The same pattern of effects was observed in other studies that showed no influence of drug withdrawal on the processing of sensory information (Abduljawad et al, 1997;Cabral et al, 2006;Fendt and Mucha, 2001;Peleg-Raibstein et al, 2006). However, there was an unexpected enhancement of the PPI during withdrawal in both sucrose and diazepam groups.…”
Section: Discussionsupporting
confidence: 86%
“…The same pattern of effects was observed in other studies that showed no influence of drug withdrawal on the processing of sensory information (Abduljawad et al, 1997;Cabral et al, 2006;Fendt and Mucha, 2001;Peleg-Raibstein et al, 2006). However, there was an unexpected enhancement of the PPI during withdrawal in both sucrose and diazepam groups.…”
Section: Discussionsupporting
confidence: 86%